THE EFFECT OF REGIONAL ORIGINAL REVENUE, POPULATION AND ECONOMIC GROWTH ON REGIONAL SPENDING - Mhd Ali Akbar (Riset Ekonomi Pembangunan, 2021)
This research aims to determine the effect of Regional Original Revenue/Pendapatan Asli Daerah (PAD, Population and Economic Growth on Regional Expenditures of North Sumatra Province in 2013-2015. The analytical method used in this research is a quantitative method with multiple linier regression by testing the classical assumptions. The results of this research concluded that the Regional Original Revenue, Population and Economic Growth significantly influence the Regional Expenditure in the Regency/City Region of North Sumatra Province. Partially Regional Original Revenue and Population have a significant influence, while Economic Growth has insignificant influence to the Regional Expenditure